2021
DOI: 10.1074/jbc.ra120.016126
|View full text |Cite
|
Sign up to set email alerts
|

The role of cysteines in the structure and function of OGG1

Abstract: 8-oxoguanine glycosylase (OGG1) is a base excision repair enzyme responsible for the recognition and removal of 8-oxoguanine, a commonly occurring oxidized DNA modification. OGG1 prevents the accumulation of mutations and regulates the transcription of various oxidative stress-response genes. In addition to targeting DNA, oxidative stress can affect proteins like OGG1 itself, specifically at cysteine residues. Previous work has shown that the function of OGG1 is sensitive to oxidants, with the cysteine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…A putative regulatory role of the detected NOS/SONOS redox switches is further supported by the high degree of conservation of the lysine–cysteine pairs in the protein orthologs (either across different domains of life or in clades of related organisms) despite the fact that in many proteins, only one of the two residues has a direct functional role required for biological activity, as reported for, for example, OGG1 or rabphilin (Supplementary Figs. 5 and 6 ) 33 , 34 .…”
Section: Resultsmentioning
confidence: 99%
“…A putative regulatory role of the detected NOS/SONOS redox switches is further supported by the high degree of conservation of the lysine–cysteine pairs in the protein orthologs (either across different domains of life or in clades of related organisms) despite the fact that in many proteins, only one of the two residues has a direct functional role required for biological activity, as reported for, for example, OGG1 or rabphilin (Supplementary Figs. 5 and 6 ) 33 , 34 .…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that OGG1 could play a protective role in inflammatory diseases. OGG1 polymorphism could offer susceptibility to lupus nephritis and modulate 8-OH-d G serum level in SLE patients [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…High SLEDAI was correlated with low serum albumin in lupus nephritis [ 15 ]. Some studies in the last few years showed that thiol-disulfides interconversion plays a crucial role in antioxidant defense, apoptosis, detoxification, transcription, enzymatic activity regulation [ 20 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A putative regulatory role of the detected NOS/SONOS redox switches is further supported by the high degree of conservation of the lysine-cysteine pairs in the protein orthologues (either across different domains of life or in clades of related organisms) despite the fact that in many proteins only one of the two residues has a direct functional role required for biological activity as reported for e.g. OGG1 or rabphilin (SI Tables 3, 4) 30,31 .…”
Section: Chemical Functions Of the Nos Lysine And Cysteine Residuesmentioning
confidence: 67%